Facilitators and barriers to neurologist referral of patients for epilepsy surgery evaluation - Chloé E. Hill; Daniel Hochster; Jessica E. Baker; Alison L. Herman; Nishad Shaheid; Susanna S. O'Kula; Jack M. Parent; Darin B. Zahuranec; Lesli E. Skolarus (Epilepsia Open)
Abstract Objective Epilepsy surgery offers a potential cure for drug‐resistant epilepsy (DRE), yet surgery is underutilized. An estimated 5% of patients with DRE undergo long‐term EEG monitoring (LTM) annually, the requisite first step of evaluation for surgical candidacy. Much of the variation in LTM referral may be attributable to individual neurologist practice rather than patient characteristics. We explored neurologist behaviors and practices in epilepsy surgery referral to guide future interventions to expand patient access to surgery. Methods This qualitative interview study recruited neurologists who treated adults with epilepsy. Interviews were grounded in the Theoretical Domains Framework (TDF) of behavior change to identify facilitators and barriers to neurologist referral for epilepsy surgery evaluation. Transcripts of semi‐structured interviews were analyzed with deductive coding guided by the TDF domains as well as emergent coding of subcodes/themes. Results Of 40 invited neurologists, 13 (33%) participated. Median time since medical school graduation was 14 years (range 5–45); four had no subspecialty training, and nine completed epilepsy/neurophysiology fellowships; nine practiced in community settings. Referral rates for presurgical evaluation ranged from less than 1 annually to 1 monthly. The most important TDF domains identified as facilitators of neurologist referral were knowledge, skills, optimism, and beliefs about capabilities. Domains identified as barriers of neurologist referral included reinforcement and environmental context and resources, both at the intersection of referring provider and epilepsy center and with regard to perceived patient burden. Social influences and social/professional role and identity operated as facilitators or barriers. Significance Looking toward future interventions to improve rates of presurgical evaluation, attention should be focused on the most pertinent and most modifiable domains. Neurologists' skills and their perception of their capabilities operate as facilitators; thus, disseminating effective communication approaches to patient discussions may support increased neurologist referral. To address environmental context & resource barriers specifically, inter‐institutional communication, presurgical evaluation pathway coordination, and resources/support for patients could be targeted to improve neurologist referral. Plain Language Summary Epilepsy surgery, while effective, is underutilized. There is variability in how individual neurologists refer patients with drug‐resistant epilepsy for epilepsy surgery. This interview study identified methods to facilitate referral for epilepsy surgery evaluation, such as improving patient/provider discussions about surgery. Several approaches could also alleviate barriers to presurgical evaluation, such as better inter‐institutional communication, expanded care coordination, and greater resources for patients.